HAIANCED SCORECARD: PENDEKATAN ALTERNATIF UNTUK PENGUKURAN KINERJA - Jurica Lucy (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2005)
Traditionally, performance measurement systems emphasize mo tv on financial indicators without linking these indicators to strategic objectives and communicating them to all levels of organizations. . I.v a ivsuh, the organizations will lose their competitive advantage. Balanced Scorecard developed by Kaplan and Norton (1992) intends to overcome the problems by incorporating tmditional measuivs of business unit perfomance and a performance measurement system driven by organizational strategies. Therefore, it incorpomtes financial, customer, internal business pivcess, and teaming and gtvwth perfomance indicators into its model. as a ivlatively a new model, the Balanced Scorecanl has gained a widespivad suppo' t as predicted by Gartner Gmup that at least 40% of Fortune l.()0() companies used the system (Frigo and Knnnwiede, 2000). It is the intention of this paper to discus v the concept and benefits of the Balanced Scorecard and difficulties that might occur in implementing it.